Factores de riesgo relacionados con el desarrollo de anemia y sus consecuencias en pacientes con IRC dializados en el Hospital Isidro Ayora - Reyes Loaiza, Mary del Pilar (2015)
The Chronic Renal insufficiency (IRC) is the progressive and irreversible deterioration of kidney function, resulting in loss of glomerular function, tubular and endocrine of the kidney. Out a large percentage of patients with Renal insufficiency undergoing dialysis suffer from anemia, adding to this risk factors that exacerbate the box such as blood loss during session of hemodialysis, coexistence of chronic diseases such as Systemic Lupus Erythematosus, Cancer, gastrointestinal diseases, liver failure. Investigative problem ¿was what is the relationship between risk factors that influence the development and consequences of anemia in patients with chronic renal failure on dialysis in the Isidro Ayora Hospital? the same as its realization is justified, given that although developing anemia is a factor of morbidity for the development of complications in patients with chronic renal failure. This study aims to identify risk factors in the development of anemia and its consequences in patients with chronic renal failure. The methodology being retroprospectivo work and descriptive research, with the implementation of a survey, training through lectures, delivery of basic material and easily understandable information In the present investigation, occurred find worthy of note, that includes 6 major risk factors that exacerbate Anemia, have been diagnosed of IRC over one year ago, receiving three session of hemodialysis per week, being within stage 5 of IRC, present Diabetes and Gastritis as associated disease, presenting pictures of infection or inflammation, and have performed any type of surgery after diagnosing IRC. Also showed that all the patients studied have Anemia chronic disease most of which belong to Anemia grade I. He was to determine some consequences resulting in anemia on IRC, as patients: lower tolerance to exercise, difficulty or limitation to perform everyday activities and presence of hypertrophic heart disease. Keywords: Chronic Renal Failure, Anemia, Hemodialysis, risk factors